English Teachers’ Perception on the Quality of Online Learning during Covid-19 - Yani, Ani (Yayasan Visi Intan Permata, 2021)
The outbreak of Covid-19 has brought forth a plethora of research exploring teachers’ and students’ perceptions and expectations on online learning. While it is ambivalent whether schools should be opened in the next academic year, it becomes pertinent to learn the opinion of teachers and to explore the degree of adaptation towards implementing online learning. This article reports a case study examining Indonesian English teachers’ perception of the quality of their online courses during the Covid-19 pandemic. The data collected for this study are survey responses from 100 English teachers of primary, secondary, and higher education from 12 cities in Indonesia. The data was analyzed using both quantitative and qualitative descriptive methods. The findings revealed that the teachers generally perceived their online learning as moderately effective. The evaluation was based on the eight general standards of online course evaluation from Quality Matters. The standards evaluating the course overview, learning objectives, course technology, learner support, and accessibility were perceived to be effective. Assessment and interaction were perceived to be moderately effective, and instructional materials as ineffective. As this study investigates the quality of online learning based on the teachers’ perspective, it did not reflect the quality of the teaching-learning process as a whole.